The influence of the parasocial relationship on the learning motivation and learning growth with educational YouTube videos in self regulated learning - Beautemps, Jacob; Bresges, André (Frontiers in Education, 2022)
Parasocial relationships (PSRs) or parasocial interactions (PSIs) have been extensively researched in the field of marketing and television. As a result, we know that viewers form strong relationships with presenters and this greatly impacts the product they sell. However, whether this effect also impacts learning through educational videos is rarely researched. In this study, the correlation between PSI and learning growth, as well as learning motivation, was investigated. The results showed no correlation between PSI and learning growth, but a slight correlation between PSI and learning motivation, especially in the case of female participants. This shows potential for the creation of educational videos. Simultaneously, the findings are important for the training of teachers, because through research on PSI we understand the factors that can lead to the improvement of interaction and relationships.